The Influence of Gadget Use and Teacher Creativity Through Motivation on Students Learning Outcomes of Science - Muhammad Iqbal; Rosma Diana Lubis; Sri Wahyuni (Postgraduate, University of Mataram, 2024)
This research aims to provide empirical evidence regarding the influence of gadget use and teacher creativity through motivation on learning outcomes in class VI students at SD Negeri 10 Bebesen. In this research, the author used secondary data and primary data. Secondary data was obtained from the Central Aceh District Education Office, while primary data was obtained from questionnaires for students at SD Negeri 10 Bebesen. The analysis model used is path analysis with a t-test, F-test, and coefficient of determination test. Based on partial test results (t-test) it shows that the use of gadgets has a positive and significant effect through motivation on the learning outcomes of Class VI students at SD Negeri 10 Bebesen, this is proven by the calculated t value (1.95) which is greater than the t table (1.67) with a value significance (0.01) is smaller than the significance limit (0.05). Teacher Creativity has a positive and significant effect through Motivation on Class VI Student Learning Outcomes at SD Negeri 10 Bebesen, this is proven by the calculated t value (1.82) which is greater than the t table (1.67) with a significance value (0.01) which is smaller than the significance limit (0.05).